Failed information transfer about the church: An analysis of present-day cartoons about religious plurality at school (Pedagogical Horizons, 2021)
The article focuses on the social construction of religious plurality within the school-context on the level of social discourses. In other words: What type of significance do societal discussions ascribed to religious plurality within the school-context? To answer this question, the article deals with present-day school-cartoons that have religion as a topic. The analyses highlight the multifold dimensions of the discursive construction of religion at school. Nevertheless, religious plurality is only a marginalized topic. The cartoons reduce the role of religion at school primary to (failed) attempts to transfer knowledge about religion.
Keywords: Religious Plurality; Jokes; Cartoons; School